The ethics of consent theory and practice - Miller, Franklin G.; Wertheimer, Alan. (New York ; Oxford : Oxford University Press, 2010)
Consent is a basic component of the ethics of human relations making permissible a wide range of conduct that would otherwise be wrongful. Consent marks the difference between slavery & employment, permissible sexual relations & rape, borrowing or selling & theft, medical treatment & battery, participation in research & being a human guinea pig.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Consent (Law); Informed consent (Medical law); Ethics; Medical ethics